Against all odds: a qualitative exploration of how adolescent mothers become career women - Ngafeeson, Vincent (My University, 2025)
Background: Adolescent motherhood presents significant challenges, including socio-cultural, economic, systemic, and educational barriers that can impede long-term success. Despite these obstacles, some adolescent mothers transition into successful career women. Understanding how these women overcome such barriers is important for developing strategies to support current and future adolescent mothers. Objective: This study explored the trajectories of career women who were once adolescent mothers, focusing on how they found the motivation to overcome various barriers and achieve career success. It sought to identify common themes and strategies that can inform support programs for adolescent mothers. Methods: This study employed a qualitative research design rooted in a phenomenological approach. Five participants who became mothers during adolescence and are now regarded as career women were recruited through purposive sampling. Data were gathered through in-depth, semi-structured interviews conducted via Zoom. The interviews focused on participants' experiences, challenges, sources of motivation, and support systems. Data was analyzed using the Interpretative Phenomenological Analysis (IPA) to uncover themes and patterns. Results: The interviews produced three main themes: Unyielding Resolve, Resourcefulness and Strategic Prioritization, and Urgency as a Catalyst for Personal Growth and Change. These themes highlight the participants' determination, strategic efforts, and proactive approaches to personal development. Conclusion: The study sheds light on the remarkable journeys of adolescent mothers who have successfully transitioned into career women. The findings underscore the crucial role of intrinsic and extrinsic motivations, as well as the significance of relatedness, autonomy, and competence in the career development of adolescent mothers.
Keywords: Career woman; Intrinsic motivation; Extrinsic motivation; Autonomy; Competence; Relatedness